IMPROVING VOCABULARY MASTERY BY USING SHORT STORIES - Nasria; Muhammad Ihsan; Andi Muhammad Dakhalan (Datokarama English Education Journal, 2022)
This research aims to find out whether short stories can be successful in improving students' vocabulary mastery or not. The researcher used quantitative research with experimental design using one-group-pretest-posttest. The sample of this research is class XI IPA 2 students of SMA Negeri 6 Palu that consists of 15 students. This class is taken as the experimental class, and the class is taught by using a short story, specifically about the legend. The selection of samples in this research used purposive sampling. After conducting the test, the researcher got the mean score of the students' pre-test is 48.33 while the average score of the post-test is 74.00. Then the data were analyzed using the t-test formula. The result of data analysis shows that t-count was greater than t-table, t-count = 6.282 and t-table = 1.771 at a significance level of 0.05. It can be concluded that there is a significant improving in students' vocabulary mastery after using short stories as learning materials.